2014
DOI: 10.1016/j.bbrc.2014.09.094
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine promotes autophagy in skeletal muscle cells by increasing the calcium-dependent activation of AMP-activated protein kinase

Abstract: Caffeine has been shown to promote calcium-dependent activation of AMP-activated protein kinase (AMPK) and AMPK-dependent glucose and fatty acid uptake in mammalian skeletal muscle. Though caffeine has been shown to promote autophagy in various mammalian cell lines it is unclear if caffeine-induced autophagy is related to the calcium-dependent activation of AMPK. The purpose of this study was to examine the role of calcium-dependent AMPK activation in regulating caffeine-induced autophagy in mammalian skeletal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 25 publications
2
23
0
3
Order By: Relevance
“…We previously demonstrated that caffeine primarily increases AMPK activation in a CaMKKβ-dependent manner in skeletal myotubes (Mathew et al 2014). In the current study, we discovered that the addition of 30 μM STO609 prevented the significant (P < 0.05) reduction in P-S6K1 (Thr389) and P-4EBP1 (Thr37/46) in caffeine vs. vehicle treated skeletal myotubes (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously demonstrated that caffeine primarily increases AMPK activation in a CaMKKβ-dependent manner in skeletal myotubes (Mathew et al 2014). In the current study, we discovered that the addition of 30 μM STO609 prevented the significant (P < 0.05) reduction in P-S6K1 (Thr389) and P-4EBP1 (Thr37/46) in caffeine vs. vehicle treated skeletal myotubes (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, activated mTORC1 phosphorylates the eukaryotic translation initiation factor 4E-binding protein 1 (4EBP1), which prevents 4EBP1 from associating with and thus repressing the eukaryotic translation initiation factor 4E (eIF4E) from recruiting the 40S ribosomal subunit to the 5′ end of mRNA (Csibi et al 2010). The AMP-activated protein kinase (AMPK) directly inhibits the activation of mTORC1 in skeletal muscle cells (Mounier et al 2009a, b), and caffeine has been shown to significantly increase AMPK activation in skeletal muscle cells (Egawa et al 2011a, b; Mathew et al 2014). Though caffeine has been shown to significantly reduce mTORC1 activation in numerous mammalian cell lines, it remains unclear if caffeine reduces protein synthesis in skeletal muscle cells in an AMPK-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The total protein concentration of each sample was determined using a Bradford assay. Western blot analysis was conducted using a previously described protocol [26]. Blots were developed using standard ECL detection and images were acquired on a FluorChem E System imager (ProteinSimple, Santa Clara, CA, USA).…”
Section: Methodsmentioning
confidence: 99%